Parental Awarness of Prose Literacy for Class 3 Elementary School in Semampiran Hamlet, Ketundan Village, Pakis District, Magelang Regency - Rahmawati, Arifa; Septiyani, Tuti; Ismail, Muhammad Ghofir; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the level of parental awareness of children’s prose literacy in Semampiran Hamlet, Ketundan Village, Pakis District, Magelang Regency. This study uses a survey methodology. The data collection technique is the questionnaire value given by the researcher to the research subject. Based on the results of the data, it can be concluded that students have problems in their prose literacy. Parents do not fully support students in developing their literacy with the lack of storytelling mentoring activities. Children also experience limited and delayed reading activities. As a result, students have low reading comprehension and need time to understand a story text.